2021
DOI: 10.33087/jmas.v6i2.276
|View full text |Cite
|
Sign up to set email alerts
|

Capital Structure Conditions Affected by Company Internal Factors: a Case Study of Non-Cyclicals Consumer Companies on Indonesian Stock Exchange

Abstract: The purpose of this research is to find out how the variables of firm size, asset structure, profitability, liquidity, and sales growth influence the capital structure of non-cyclical consumer companies listed on the Indonesia Stock Exchange. The population in this study was 55 non-cyclical consumer companies listed on the Indonesia Stock Exchange in 2015 - 2019, while for the method of determining the sample in this study using a purposive sampling technique, as many as 25 companies. The analytical technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…The results of this research are in line with research by [7,35] and based on previous research, the author found that Agency Cost does not have a significant effect on Firm value. Where the higher Agency Costs incurred do not significantly influence the increase in Firm value because in terms of auditing quality the financial statements do not reflect the high share market value of companies audited by external parties.…”
Section: The Influence Of Agency Costs On Firm Value In Companies Lq45supporting
confidence: 90%
“…The results of this research are in line with research by [7,35] and based on previous research, the author found that Agency Cost does not have a significant effect on Firm value. Where the higher Agency Costs incurred do not significantly influence the increase in Firm value because in terms of auditing quality the financial statements do not reflect the high share market value of companies audited by external parties.…”
Section: The Influence Of Agency Costs On Firm Value In Companies Lq45supporting
confidence: 90%
“…The oil and gas industry invests more in working capital. In line with earlier studies, LQTY exhibits a negative connection (Rokhayati et al, 2021). FS depicts a positive relationship as expected; hence our hypothesis is not rejected.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 90%
“…Amatya (2020) further discovered an inverse correlation between LQTY and FL. The findings demonstrate that FS, AS, PFTY, LQTY, and sales growth have an adverse and notable impact on capital structure (Rokhayati et al, 2021). Relying on the literature discussed above, we suppose the LQTY factor discourages debt financing, and LQTY and FL are inversely related.…”
Section: Liquidity and Capital Structurementioning
confidence: 69%
“…Penyesuaian yang berasal dari internal perusahaan dapat berupa peneyesuaian dari struktur modal perusahaan. Menurut Dewi (2019); Rokhayati (2021), masalah kebutuhan dana dan persediaan modal adalah masalah yang penting karena menyangkut struktur modal perusahaan yang mana mencerminkan kondisi keuangan perusahaan. Sutrisno (2017) menyatakan struktur modal merupakan imbangan antara modal asing atau hutang dengan modal sendiri.…”
Section: Pendahuluanunclassified